Two-Phase Modeling Technology and Subsection Modeling Method of Natural Gas Hydrate: A Case Study in the Shenhu Sea Area - Liu, Fang; Liang, Jinqiang; Lai, Hongfei; Han, Lei; Wang, Xiaoxue; Li, Tingwei; Wang, Feifei (Frontiers in Earth Science, 2022)
It is found that natural gas hydrate is not only a pore-filling material but also exists in the reservoir in the form of rock skeleton particles. Therefore, the traditional petrophysical simulation method cannot well describe the physical properties of natural gas hydrate reservoir. At the same time, the physical properties of the hydrate layer and its associated free gas layer are quite different, so it is difficult to fit the physical properties of the two media using traditional modeling methods. The two-phase modeling technology used in this paper is the equivalent medium modeling technology based on BK solid substitution theory and Gassmann fluid substitution theory, which simulates hydrate particles in rock skeleton and hydrate filling in pores, respectively. The forward simulation results show that the two-phase simulation technology of natural gas hydrate can well fit the P-wave and S-wave velocity information of the medium. At the same time, the equivalent medium model of the free gas reservoir is established by using only Gassmann fluid substitution theory. The practical application shows that the subsection modeling method can well solve the problem of the too large difference between the two sets of reservoir physical properties and make the calibration results of forward modeling synthetic records more accurate.